Pengaruh Inflasi, Kebijakan Moneter dan Pengangguran Terhadap Perekonomian Indonesia - Yenni Del Rosa; Imran Agus; Mohammad Abdilla (Universitas Dharma Andalas, 2019)
The purpose of this study was determine the effect of macro economics are inflation, interest rate, unemployment and growth of economics in Indonesia. This data used are time series data from 2000 – 2018 per semester. The amount of adjusted R square is 0,51026 = 51,026% which means that independent variables can explain changes in economics growth variables of 51,026% while the rest of 48,974% explained by other factors in this study. This research shows only interest rate and unemployment variables influence significantly to economics of growth and inflation is no influence significantly to economics of growth in Indonesia with multiple linier regression equation Y = -1,80733 – 0,18059X1 + 0,14194X2 + 1,26385 X3 + e.